Hemodynamic Resuscitation Characteristics Associated with Improved Survival and Shock Resolution After Cardiac Arrest. Issue 6 (June 2016) - Janiczek, Jonathan A.; Winger, Daniel G.; Coppler, Patrick; Sabedra, Alexa R.; Murray, Holt; Pinsky, Michael R.; Rittenberger, Jon C.; Reynolds, Joshua C.; Dezfulian, Cameron
ABSTRACT: Purpose: To determine which strategy of early post-cardiac arrest hemodynamic resuscitation was associated with best clinical outcomes. We hypothesized that higher mean arterial pressure (MAP) achieved using IV fluids over vasopressors would yield better outcomes. Methods: Retrospective cohort study of post-cardiac arrest patients between March 2011 and June 2012. Patients successfully resuscitated from cardiac arrest, admitted to an intensive care unit and surviving at least 24 h, were included. Patients missing data for >2 h after return of spontaneous circulation were excluded. The institutional standard for post-resuscitation MAP was ≥65 mm Hg with no guidelines on how MAP was supported. We examined the association between early (6 h) average MAP, vasopressor use summarized as cumulative vasopressor index and fluid intake with outcomes including survival to discharge, favorable neurologic outcome based on Cerebral Performance Category 1 or 2, and the surrogate outcome measure of lactate clearance using Pearson correlation and multivariable regression. Results: Of 118 patients, 55 (46%) survived to hospital discharge, 21 (18%) with favorable neurologic outcome. Higher 6-h mean cumulative vasopressor index was independently associated with worsened survival (OR 0.67; 95% CI 0.53, 0.85; P = 0.001). Resuscitation subgroups receiving higher than median vasopressors had worsened survival to hospital discharge regardless of fluid intake. In addition, higher MAP-6h correlated with increased lactate clearance ( r = 0.29; P = 0.011). Conclusions: Early post-return of spontaneous circulation hemodynamic resuscitation achieving higher MAP using fluid preferentially over vasopressors is associated with improved survival to hospital discharge as well as better lactate clearance.